The effect of tea on iron absorption. Issue 3 (March 1975) - Disler, P B; Lynch, S R; Charlton, R W; Torrance, J D; Bothwell, T H; Walker, R B; Mayet, F
Abstract : The effect of tea on iron absorption was studied in human volunteers. Absorption from solutions of FeCl3 and FeSO4, bread, a meal of rice with potato and onion soup, and uncooked haemoglobin was inhibited whether ascorbic acid was present or not. No inhibition was noted if the haemoglobin was cooked. The effect on the absorption of non-haem iron was ascribed to the formation of insoluble iron tannate complexes. Drinking tannin-containing beverages such as tea with meals may contribute to the pathogenesis of iron deficiency if the diet consists largely of vegetable foodstuffs.